Sosialisasi Dan Edukasi Tentang Keterbukaan Informasi Publik Serta Pembentukkan Kelompok Masyarakat Peduli Informasi Di Kelurahan Menteng Kota Palangka Raya - Srie Rosmilawati; Annisa Rizki Ananda; Sirajul Rahman; Indah Tri Handayani; Milka Milka (UNIVERSITAS MUHAMMADIYAH MATARAM, 2022)
Every citizen has the right to know the reasons for public policies by a public body. Which before the Reformation, this substance was almost non-existent and did not apply in our country. On the other hand, there is also a new paradigm in Public Bodies after the birth of the UU KIP, before the reform of all information and every policy in a closed public agency, it is difficult to know the performance of high-ranking officials in a public agency, all governance of a public agency is closed and not informed to the public. , for example budget, procurement of goods and services, and others. Based on this, it is necessary to provide education from the Information Commission in terms of providing information disclosure through outreach activities. regarding the importance of information disclosure to the public, so that people know their rights in finding, storing, processing information for themselves and their social environment as well as their role in supervising any information in public bodies in Central Kalimantan. Implementation carried out in the program includes preparation, coordination, opening and socialization, implementation of outreach and education activities on Public Information Disclosure and the Establishment of Information Concerned Community Groups (KMPI) in Menteng Village, Palangka Raya City. In the socialization the community was taught how to obtain public information by the Central Kalimantan Information Commission and also how to resolve public information disputes through the Central Kalimantan Information Commission.